Emotional Intelligence as a Personal Resource of Professional Becoming of Specialists of Socionomic Professions - Breus, Yuliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article presents the theoretical analysis of the problem of emotional intelligence as a personal resource of professional becoming of specialists of socionomic professions. The author's structural-functional model of emotional intelligence is presented. It shows the levels of functioning, functional characteristics, emotional competencies and substantial characteristics of emotional intelligence. The influence of emotional competences on professional activities of specialists of socionomic professions is analyzed. Such emotional competences are described: the ability to understand own emotions and emotions of others, the ability to demonstrate emotional attitude to situations and other people adequately; the productive interaction and psychological flexibility in relations with others.